AGROCHEMICAL EFFECTIVENESS CALCIUM CHLORINE – MAGNESIUM DEFOLIANT (Scientific journal of the Fergana State University, 2024)
Defoliation of raw cotton is one of the most important agrotechnical measures that allows harvesting in the pre-frost period. However, many factors influence the effectiveness of defoliation. The effectiveness of defoliant FanDef in cotton varieties S - 6524, Namangan - 77, AN - 36 and Navruz (5.0-7.0 l/ha), grown in various soil conditions of the republic (Tashkent, Andijan and Fergana regions) in 2010 - 2014 years.